Intrabronchial Microdialysis: Effects of Probe Localization on Tissue Trauma and Drug Penetration into the Pulmonary Epithelial Lining Fluid. Issue 4 (17th April 2015) - Rottbøll, Lisa Amanda Holm; Skovgaard, Kerstin; Barington, Kristiane; Jensen, Henrik Elvang; Friis, Christian
Abstract Recent intrabronchial microdialysis data indicate that the respiratory epithelium is highly permeable to drugs. Of concern is whether intrabronchial microdialysis disrupts the integrity of the respiratory epithelium and thereby alters drug penetration into the pulmonary epithelial lining fluid (PELF). The objective of this study was to investigate the effect of intrabronchial microdialysis on the integrity of the bronchial epithelium. Microdialysis sampling in PELF in proximal (n = 4) and distal bronchi (n = 4) was performed after intravenous inulin and florfenicol administration in anaesthetized pigs. Inulin was used as a marker molecule of permeability of the epithelium, and florfenicol was used as test drug. Bronchial tissue was examined by histopathology (distal and proximal bronchi) and gene expression analysis (RT‐qPCR, proximal bronchi) at the termination of the experiment (6.5 hr). The microdialysis probe caused overt tissue trauma in distal bronchi, whereas no histopathological lesions were observed in proximal bronchi. A moderate up‐regulation of the pro‐inflammatory cytokines IL1B, IL6 and acute‐phase reactant serum amyloid A was seen in proximal bronchi surrounding the microdialysis probes suggesting initiation of an inflammatory response. The observed up‐regulation is considered to have limited impact on drug penetration during short‐term studies. Inulin penetrated the respiratory epithelium in both proximal and distal bronchi without any correlation to histopathological lesions. Likewise, florfenicol penetration into PELF was unaffected by bronchial histopathology. However, this independency of pathology on drug penetration may not be valid for other antibiotics. We conclude that short‐term microdialysis drug quantification can be performed in proximal bronchi without disruption of tissue integrity.